Nuclear Protein 1 Expression Is Associated with PPARG in Bladder Transitional Cell Carcinoma - Chao Lu; Shenglin Gao; Li Zhang; Xiaokai Shi; Yin Chen; Shuzhang Wei; Li Zuo; Lifeng Zhang (PPAR Research)
Background. The Nuclear protein 1 gene was first discovered in acute pancreatitis and functions as an oncogene in cancer progression and drug resistance. However, the role of Nuclear protein 1 in bladder transitional cell carcinoma (BTCC) is still unclear. Methods. The Cancer Genome Atlas database and immunohistochemical analysis were adopted to evaluate Nuclear protein 1 expression in BTCC. We applied lentivirus-mediated small-interfering RNA to down-regulate the expression of Nuclear protein 1 in BTCC cell lines. We further performed an Affymetrix microarray and Gene Set Enrichment Analysis (GSEA) to assess the genes and signaling pathways related to Nuclear protein 1. Results. We found that Nuclear protein 1 expression was up-regulated in BTCC and positively related to the degree of BTCC malignancy. Compared with Caucasian patients with BTCC, Nuclear protein 1 expression was attenuated in Asian patients. The Affymetrix microarray showed that lipopolysaccharide was the upstream regulatory factor of Nuclear protein 1 in BTCC. The GSEA indicated that Nuclear protein 1 expression was associated with signaling pathways in cancer, peroxisome proliferator-activated receptor (PPAR) pathways, and RNA degradation. The expression of Nuclear protein 1 was negatively correlated with PPARG (R=−0.290, P<0.001), but not with PPARA (R=0.047, P=0.344) and PPARD (R=−0.055, P=0.260). Conclusions. The study findings indicate that Nuclear protein 1 is positively associated with the malignancy degree of BTCC and that Nuclear protein 1 expression is negatively correlated with PPARG.